Targeting PDPN enhances antitumor T-cell activity by disrupting β-catenin-mediated PD-L1 expression in melanoma - Feng, Chunyan; Liu, Yueyue; Zhong, Xinyue; Wei, Zhenzhen; Cui, Hongjing; Yi, Jianfeng (Frontiers in Immunology, 2026)
IntroductionMelanoma is a highly immunogenic and aggressive malignancy characterized by pronounced intratumoral lymphocytic infiltration and significant responsiveness to immunotherapeutic interventions. The oncogenic glycoprotein podoplanin (PDPN) is commonly overexpressed in various cancer types, where it facilitates metastatic dissemination through interactions with CLEC-2 on platelets and other stromal cells, thereby contributing to stromal immunosuppression. Although the protumoral roles of PDPN are well documented, its precise mechanistic contributions to immune evasion in melanoma remain only partly defined and require further elucidation.MethodsTo clarify the immunological role of PDPN in melanoma, multiplex immunofluorescence staining was performed on human tissue microarrays, and bioinformatic analyses were conducted to determine the associations of PDPN with PD-L1 expression and CD8+ T cell infiltration. The therapeutic efficacy and underlying mechanisms of the PDPN-targeting inhibitory peptide CY12-RP2 were systematically evaluated using flow cytometry, Western blotting, ELISA, and in vivo studies in both immunodeficient and immunocompetent mouse models. These comprehensive analyses demonstrated that targeting PDPN with CY12-RP2 can reestablish antitumor immunity.ResultsMulti-omics analyses indicated that PDPN expression is highly correlated with immune checkpoint markers, most notably PD-L1 (r = 0.504, p < 0.001), and displays an inverse relationship with the infiltration of intratumoral cytotoxic immune cells. Single-cell and spatial transcriptomic profiling revealed that PDPN supports the exclusion of CD8+ T cells and enhances the prevalence of immunosuppressive cell populations. CY12-RP2 resulted in a 60.6% reduction in tumor growth in immunocompetent murine models and reversed immune evasion by attenuating PDPN-dependent, β-catenin-mediated upregulation of PD-L1. Treatment with CY12-RP2 broadly activated antitumor immune responses, as evidenced by increased intratumoral infiltration of CD8+ T cells, elevated granzyme B production by CD8+ T cells, and enhanced secretion of pro-inflammatory cytokines (IFN-γ, TNF-α, and IL-1β). Depletion experiments confirmed that the antitumor efficacy of CY12-RP2 was entirely dependent on CD8+ T cells, establishing a CD8+ T cell-dependent mechanism of action.DiscussionThese findings identify PDPN as a critical driver of immune evasion in melanoma via b-catenin-mediated PD-L1 upregulation. Inhibitory targeting of PDPN with CY12-RP2 represents a promising therapeutic approach capable of disrupting this immunosuppressive pathway and reversing tumor immune escape.